2020
DOI: 10.5672/apunts.2014-0983.es.(2020/2).140.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Most Demanding Passages of Official Matches and Training Drills in Elite Roller Hockey

Abstract: The aim of this research was to identify and compare the most demanding passages (MDP) in elite roller hockey in competition and in different training situations. Data were collected using WIMU PRO™ sensors with inertial micro-technology and ultra-wide band positioning. Eight professional roller hockey players from the Spanish First Division League (Ok Liga) were analysed during the 2017-2018 season. The MDP were studied using a rolling average method in which maximal values were calculated for three different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…This seems to be a common concern for most practitioners who, regardless of the method, have sought to develop alternative approaches to identify the most demanding scenario of match play, since such consideration seems to contribute to the implementation of a more accurate training program prescription (Gabbett et al, 2012). Rolling average methods have commonly been used to describe the peak periods of competition in different sports such as Australian football (Delaney et al, 2017), soccer (Malone et al, 2015;Martín-García et al, 2020), basketball (Vázquez-Guerrero et al, 2020), and rink hockey (Fernández et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This seems to be a common concern for most practitioners who, regardless of the method, have sought to develop alternative approaches to identify the most demanding scenario of match play, since such consideration seems to contribute to the implementation of a more accurate training program prescription (Gabbett et al, 2012). Rolling average methods have commonly been used to describe the peak periods of competition in different sports such as Australian football (Delaney et al, 2017), soccer (Malone et al, 2015;Martín-García et al, 2020), basketball (Vázquez-Guerrero et al, 2020), and rink hockey (Fernández et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…the authors collected information from 8 players and concluded that regarding external load competition demands, the distance travelled by a rink hockey player was clearly lower than in outdoor sports [46,47]. However, in another study, performed with the same positional system and the same sample of players, Fernández et al [24] collected positional data to determine the most demanding passages through the distance covered in high-speed skating (> 18 km • h -1 ) during a match, and also in training drills. the authors concluded that they could not reproduce the most demanding passages of the match in training situations.…”
Section: Activity Profilementioning
confidence: 95%
“…Within descriptive approaches, most of the researchers sought to study age-related differences in under-17 (U-17) [18][19][20], under-20 (U-20), and senior players [17,[21][22][23][24][25]. In these studies, the authors focused their attention mainly on: (1) ball possession [17-22, 26, 27];…”
Section: Major Research Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the use of technology in certain team sports modalities has increased in the last decade, research into conditional demands is scant. Some research has addressed official matches (Merino Tantiña et al, 2014;Fernández et al, 2020b) and the most demanding passages in certain drills (Fernández et al, 2020a), although microcycle training load dynamics has never been described.…”
Section: Introductionmentioning
confidence: 99%